A comparison of dimensional and discrete models for the representation of perceived and induced affect in response to short musical sounds - Korsmit, Iza Ray; Montrey, Marcel; Wong-Min, Alix Yok Tin; McAdams, Stephen (Frontiers in Psychology, 2023)
In musical affect research, there is considerable discussion on the best method to represent affective response. This discussion mainly revolves around the dimensional (valence, tension arousal, energy arousal) and discrete (anger, fear, sadness, happiness, tenderness) models of affect. Here, we compared these models' ability to capture self-reported affect in response to short, affectively ambiguous sounds. In two online experiments (n1 = 263, n2 = 152), participants rated perceived and induced affect in response to single notes (Exp 1) and chromatic scales (Exp 2), which varied across instrument family and pitch register. Additionally, participants completed questionnaires measuring pre-existing mood, trait empathy, Big-Five personality, musical sophistication, and musical preferences. Rater consistency and agreement were high across all affect scales. Correlation and principal component analyses showed that two dimensions or two affect categories captured most of the variation in affective response. Canonical correlation and regression analyses also showed that energy arousal varied in a manner that was not captured by discrete affect ratings. Furthermore, all sources of individual differences were moderately correlated with all affect scales, particularly preexisting mood and dimensional affect. We conclude that when it comes to single notes and chromatic scales, the dimensions of valence and energy arousal best capture the perceived and induced affective response to affectively ambiguous sounds, although the role of individual differences should also be considered.In two online experiments, we systematically varied stimulus length from single notes (Exp 1) to 15note chromatic scales (Exp 2). Different groups of participants rated affect on three dimensional scales (valence, tension arousal, and energy arousal) or five discrete scales (anger, fear, sadness,